2018
DOI: 10.11113/lspi.v5n1.61
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Writing Competencies Expected by Industries in an Exit Test

Abstract: The writing component of the Test of English Communication Skills for Graduating Students (UTM-TECS) measures competencies of understanding of task and situation, critical creative thinking, analysis and evaluation of task, choice of lexis, accuracy and clarity of expressions and coherent flow of ideas. Five years into its implementation, a revisit of the requirements was made to reassess the validity of this measurement. The methodology comprises two stages. First, it involved test design, assessment of scrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This is because the approach mitigates the apprehension of writing. Regarding this, Stapa (2008), Prasetyningrum et al ( 2021), and Ali Fuat Arici (2015) suggested that the process writing approach is more effective than the product approach in reducing writing apprehension. The findings also affirmed implementing a process-based approach to writing to reduce the frequency of errors committed, leading to minimizing writing anxiety.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%
“…This is because the approach mitigates the apprehension of writing. Regarding this, Stapa (2008), Prasetyningrum et al ( 2021), and Ali Fuat Arici (2015) suggested that the process writing approach is more effective than the product approach in reducing writing apprehension. The findings also affirmed implementing a process-based approach to writing to reduce the frequency of errors committed, leading to minimizing writing anxiety.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%